317OAssociation of survival and blood-based genomic signature with atezolizumab for patients with second-line and third-line EGFR wild-type non-small cell lung cancer: Pooled analysis of individual patient data from the POPLAR and OAK trials. (24th November 2019) - Yu, Y; Li, A; Chen, Y; Li, Q; Ou, Q; Lin, D; Zhang, W; Li, Z; Hu, H; Yao, H
Abstract: Background: Individual patient data from two multicentre, randomised trials comparing atezolizumab with docetaxel in previously treated advanced non-small-cell lung cancer (NSCLC) were analyzed to identify any preferable therapeutic approaches for patient subsets stratified by EGFR mutation status. Methods: We pooled 1, 137 patients from the phase II POPLAR trial (NCT01903993) and the phase III OAK trial (NCT02008227). Patients were randomly assigned to receive either atezolizumab or docetaxel and were analyzed based on stratification of EGFR mutation status. We built a novel algorithm integrating the blood-based tumor mutation burden and the ctDNA maximum somatic allele frequency (bTMB-MSAF score) and developed a novel clinicopathologic-genomic nomogram to predict individual survival. Results: In the whole intention-to-treat population, OS was significantly longer with atezolizumab than with docetaxel (hazard ratio [HR] 0.72, P < 0.001). Among patients without EGFR or ALK mutations, overall survival (OS) was significantly longer with atezolizumab than with docetaxel (HR 0.67; P < 0.001); patients with a bTMB-MSAF score<20 showed improvement in OS (HR 0.56; P < 0.001) and progression-free survival (PFS) (HR 0.74; P = 0.0023), and these patients who concurrently had programmed death ligand 1 (PD-L1) expressing on over 50% tumor cells or over 10% of tumor-infiltrating immune cells (TC3 or IC3) had the greatest OS improvements (HR 0.44; P = 0.007) and promising PFS benefits (HR 0.54; P = 0.019). EGFR mutant patients could not gain significant OS or PFS benefits from atezolizumab over docetaxel, irrespective of PD-L1 expression and bTMB-MSAF score. Patients with low-risk scores had longer OS (HR 0.17; P < 0.001; AUC=0.912 for 3-year OS) than patients with high-risk scores classified by the nomogram. Conclusions: Atezolizumab showed better OS and PFS than docetaxel in previously treated EGFR wild-type NSCLC patients with a bTMB-MSAF score < 20, especially in those with PD-L1 expression of TC3 or IC3. Our clinicopathologic-genomic nomogram is effective in predicting survival of NSCLC patients undergoing atezolizumab. Clinical trial identification: NCT01903993 and NCT02008227. Legal entity responsible for the study: Herui Yao. Funding: Herui Yao is funded by the National Science and Technology Major Project under Grant [2020ZX09201021]; National Natural Science Foundation of China under Grant [81372819, 81572596, U1601223]; Natural Science Foundation of Guangdong Province under Grant [2017A030313828]; and Guangzhou Science and Technology Program under Grant [201704020131]. Disclosure: All authors have declared no conflicts of interest.